2014
DOI: 10.4103/2229-5186.129331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of menopause on lipid profile in relation to body mass index

Abstract: The risk of coronary artery disease (CAD) increases in women after menopause. [1,5] In addition, recent evidence Effect of menopause on lipid profile in relation to body mass indexAbstract Background: Menopause is a natural event in the ageing process and signifies the end of reproductive years with cessation of cyclic ovarian function as manifested by cyclic menstruation. Lipid profile is altered in menopause because of various reasons. Objectives: The study was aimed to compare the lipid profile in women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Analogous findings were observed by Bade S and SHAH S [26].They found that, "the levels of TC (246.62 ± 29.19mg %) and TG (131.22±18.99mg %) were significantly higher in post-menopausal women than those of pre-menopausal counterparts (P < 0.05). HDL-C levels were significantly lower (moderate risk category P <0.001) and LDL-C (224.21±30.98mg %) levels were also significantly higher in postmenopausal group.…”
Section: Discussionsupporting
confidence: 78%
“…Analogous findings were observed by Bade S and SHAH S [26].They found that, "the levels of TC (246.62 ± 29.19mg %) and TG (131.22±18.99mg %) were significantly higher in post-menopausal women than those of pre-menopausal counterparts (P < 0.05). HDL-C levels were significantly lower (moderate risk category P <0.001) and LDL-C (224.21±30.98mg %) levels were also significantly higher in postmenopausal group.…”
Section: Discussionsupporting
confidence: 78%
“…31 On the other hand recent studies reported that obesity as a common risk for breast cancer and dyslipidemia. 18,33,34 This could be due to adiposity-related secretion of estrogen, increases in circulating insulin and insulin-like growth factors, local production of adipokines and leptin that could stimulate the breast cell growth. 35 In addition, obesity decreases the production of sex hormone-binding globulin which in turn results foran increased biologically active unbound form of estrone and estradiol which promotes cell growth and metastatic potential in breast tumor.…”
mentioning
confidence: 99%
“…16 Lipid profile is altered in menopause because of various reasons especially the changes in hormone levels which control most other metabolic activities of the human body like the estrogen. 17 This study at baseline revealed that serum levels of TG, LDL-C and VLDL-C were higher in postmenopausal women when compared to the levels after the intervention with honey. The alteration in lipid profile may be due to impairment in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 75%
“…16 Lipid profile have been found to be altered in menopause because of various reasons especially the changes in hormone levels which control most other metabolic activities of the human body like the estrogen. 17 The study therefore seeks to elucidate the changes in lipid profile of menopausal women after treatment with honey for four months.…”
Section: Introductionmentioning
confidence: 99%